2020
DOI: 10.3389/fchem.2020.610232
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional, Copper-Doped, Mesoporous Silica Nanosphere-Modified, Bioceramic Scaffolds for Bone Tumor Therapy

Abstract: In the traditional surgical intervention procedure, residual tumor cells may potentially cause tumor recurrence. In addition, large bone defects caused by surgery are difficult to self-repair. Thus, it is necessary to design a bioactive scaffold that can not only kill residual tumor cells but also promote bone defect regeneration simultaneously. Here, we successfully developed Cu-containing mesoporous silica nanosphere-modified β-tricalcium phosphate (Cu-MSN-TCP) scaffolds, with uniform and dense nanolayers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Ma et al developed bifunctional scaffolds by coating 5% Cu-containing- mesoporous silica nanosphere (MSN) on the surface of β-TCP by spin coating [ 45 ]. The scaffolds effectively obliterated tumor cells and favored osteogenic differentiation in vitro.…”
Section: Bioceramic Scaffoldsmentioning
confidence: 99%
“…Ma et al developed bifunctional scaffolds by coating 5% Cu-containing- mesoporous silica nanosphere (MSN) on the surface of β-TCP by spin coating [ 45 ]. The scaffolds effectively obliterated tumor cells and favored osteogenic differentiation in vitro.…”
Section: Bioceramic Scaffoldsmentioning
confidence: 99%
“…244 The above MSN is meaningful for fabricating multifunctional 3D-printed bioceramic scaffolds for treating osteosarcoma. MSN can be loaded into 3D-printed bioceramics by a simple spin-coating method, 17 which does not require chemical modification, high temperature, or pressure conditions and can retain the properties of MSN well. 246 Therefore, the MSN conjugated with -SNO and photothermal agents by sulfidation or loaded with various functional agents through its mesoporous structure is expected to realize multifunctional scaffolds integrating several therapies.…”
Section: A New Use Of An Old Approach: Chemotherapymentioning
confidence: 99%
“… [ 71 ] Cu-MSN-TCP scaffold Cu-MSN β -TCP PTT Cu-MSN could upregulate the expression of osteogenic-related genes. [ 72 ] Bifunctional scaffold Therapeutic agents Scaffold material Tumor therapy method Effect of therapeutic agents on osteogenesis Ref. α -TCP/CS/Fe 3 O 4 /GO scaffolds Fe 3 O 4 and GO α -TCP and calcium sulfate MFH Alizarin red staining demonstrated that the α -TCP/CS/Fe 3 O 4 /GO group produced more calcified nodules than the other groups.…”
Section: Bifunctional Scaffold For Tumor Therapy and Bone Regenerationmentioning
confidence: 99%